Ø§Ù„ØØ±ÙƒØ§Øª Ø§Ù„Ø£ØµÙˆÙ„ÙŠØ© Ùˆ Ø§Ù„Ø¹Ù†Ù ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© - Asmuni Muhammad Thahir (Millah: Journal of Religious Studies, 2003)
The violence phenomenon, which are conducted by some group of Islamic radicalism always luster in many countries. Some writers identified that the rational background of that actions was sociologically than the religious background of the social condition of rising of the movement. However, even though this opinion supported by many arguments, actually the violence conducted by the radical fundamentalism group caused by the texts interpretation that indicate the eclecticism toward the prophet, companions, and the people of the Muslim their selves. In the other hand,Â  there are several texts of holly book have the absolute truth related the superiority and the characteristic of Islam as the last of heaven religions. This, has caused the coming of Islamic radicalism movement in some Muslim countries like in Egypt, Pakistan, Iran, and soon.